The Effects of P5CR Gene Function of Endophytic Fungus Alternaria oxytropis OW7.8 on Swainsonine Biosynthesis - Fan Yang; Yinzhe Li; Ping Lu; Yu Wang; Feng Gao; Bo Yuan; Ling Du; Yuling Li; Kai Jiang (Biomolecules)
Locoweeds, including Oxytropis and Astragalus species, are globally recognized as plants containing swainsonine (SW), a neurotoxic alkaloid that induces neurological dysfunction and growth inhibition in livestock. SW is produced by endophytic fungi in plants; the pyrroline-5-carboxylate reductase (P5CR) gene is critical in the fungal SW biosynthetic pathway. In this study, a P5CR gene knockout mutant (ΔP5CR) was constructed from the endophytic fungus Alternaria oxytropis OW7.8 isolated from Oxytropis glabra. Compared to the wild-type strain (A. oxytropis OW7.8), the SW content in the ΔP5CR mycelia was significantly reduced, indicating that the P5CR gene plays a crucial role in promoting SW biosynthesis. Compared to the wild-type strain A. oxytropis OW7.8, the ΔP5CR mutant exhibited distinct morphological alterations in both colony and mycelial structures. The transcriptomic analysis of A. oxytropis OW7.8 and ΔP5CR revealed the downregulation of six genes associated with SW biosynthesis. Metabolomic profiling further demonstrated altered levels of six metabolites linked to SW synthesis. These findings provide foundational insights into the molecular mechanisms and metabolic pathways underlying SW biosynthesis in fungi. They hold significant value for future strategies to control SW in Oxytropis glabra and contribute positively to the protection and sustainable development of grassland ecosystems.